Studies in Ancient Technology. Vol. VIII - Forbes, R. J. (1964)
Synopsis of Early Metallurgy – Old Tools and New Methods – The Evolution of the Smith, his Social and Sacred Status – Tools and Methods of Early Metallurgy – Gold – Silver and Lead – Zinc and Brass.